Lentivirus-mediated antagomir expression for specific inhibition of miRNA function - Scherr, Michaela (Oxford University Press, 2007)
Micro RNAs (miRNA) regulate gene expression by hybridization and recruitment of multi-protein complexes to complementary mRNA target sequences. miRNA function can transiently be antagonized by antagomirs—chemically modified oligonucleotides complementary to individual miRNAs. Here, we describe the induction of stable loss-of-function phenotypes for specific miRNAs by lentivirus-mediated antagomir expression. Lentivirally expressed antagomirs are transcribed from a H1-promoter located within the lentiviral 3′LTR and were directed against miRNAs encoded on the polycistronic miR17-92 transcript. Functional silencing of miR-18a, miR-19b and miR-20a by the corresponding antagomirs specifically relieves miRNA-mediated reporter gene repression. Inhibition of miRNA function correlates to reduction of ‘miRNA’ amplification by miRNA-specific quantitative RT-PCR. Furthermore, protein expression of E2F-1, a known miR-20 target, is enhanced by lentivirally expressed anti-miR-20 antagomirs in a dose-dependent manner, whereas over-expression of miR-20a reduces E2F-1 levels. Finally, combined over-expression of specific miRNAs and antagomirs reveals individual and complementary functions of miR-18a and miR-20a and demonstrates specific miRNA impact on cell proliferation in a cell culture model.